Ocular injuries from exploding glass-bottled Coca-Cola® drinks in Port Harcourt, Nigeria - Pedro-Egbe CN (Dove Medical Press, 2011)
Chinyere Nnenne Pedro-Egbe, Chibuike Sydney Ejimadu, Henrietta NwachukwuDepartment of Ophthalmology, University of Port Harcourt Teaching Hospital, Port Harcourt, NigeriaBackground: Eye injuries and subsequent loss of vision from the glass and caps of exploding pressurized bottled drinks have been well reported, and as a result most developed countries now use mainly plastic bottles. In Nigeria, however, most drinks are still sold in glass bottles and ocular injuries from this source are therefore not uncommon.Aim: To retrospectively analyze ocular injuries resulting from exploding glass-bottled Coca-Cola® and propose ways of eliminating such injuries in future.Setting: Eye Clinic, University of Port Harcourt Teaching Hospital, Port Harcourt, Nigeria.Materials and methods: The medical records of all cases of ocular injury that presented at the Eye Clinic of the University of Port Harcourt Teaching Hospital over a 5-year period (January 2006 to December 2010) were retrieved and relevant data including age, sex, occupation, events surrounding bottle explosion, and type of ocular injury sustained were extracted.Results: A total of 426 cases of ocular injuries was seen during the period under review. There were 335 (78.6%) males and 91 (21.4%) females. Six patients had ocular injury from exploding glass-bottled Coca-Cola®, giving an incidence of 1.4%. The presenting visual acuities (VA) were light perception (2 cases), counting fingers (2 cases), and 1 VA of 6/24 and 1 VA of 6/12. There were 4 (66.7%) cases of corneoscleral laceration with uveal prolapse and 1 case of total hyphema.Conclusion: Because pressurized glass-bottles can explode with normal handling, legislation to ban the use of glass containers for bottling carbonated drinks will go a long way to reducing ocular morbidity from this source. Plastic bottles should be introduced as an alternative.Keywords: ocular injuries, exploding glass-bottled drink